A study on hybrid photocatalytic pre-treatment for seawater desalination by using oil palm fibre ash - Abdulkarim Abdulrahman, Mohamed Suliman (2023)
Owing to the scarcity of portable water sources and humic acid contamination, the desalination of saline water can be an alternative solution to meet its growing demand. Although several desalination methods already exist, there is a pressing need to create approaches that minimize the expense of their setup, operation, and upkeep. In this aspect, the pre-treatment of seawater by photocatalytic desalination technique can be an efficient and alternative way that requires low operational and implementation costs. Photocatalytic disinfection is gaining popularity as a simple and low-cost method for water treatment. In this work, cost-efficient and environmentally friendly hybrid TiO2- based photocatalysts were prepared and utilized. The photocatalysts with different ratios of TiO2 and oil palm fibre ash (OPFA) were prepared using wetness impregnation technique. The effect of metal doping of Fe and Ce at 5% and 10 % were also investigated. The incorporated materials were characterized by X-ray powder diffraction (XRD), scanning electron microscope with energy dispersive X-ray spectroscopy (SEM and EDX), N2 adsorption-desorption studies (BET), X-ray photoelectron spectroscopy (XPS), and diffuse reflectance UV–vis absorption spectroscopy. Moreover, X-ray fluorescence was used to determine the element and oxides of OPFA. The experiments were done in a 1000 mL Borosilicate reactor in the presence of either UV-light or visible light irradiation with wavelength 365 nm, and 420 nm respectively. Besides that, the hybrid system was equipped with a glass pyramid cover to collect the evaporated water. The results show that the activity of TiO2 for seawater pre-treatment improved significantly when the catalyst was hybrid with oil palm fiber ash (OPFA) (Ti:Ash 40:60 and Ti:Ash 60:40 photocatalysts) under UV light irradiation. It was found that the humic acid was significantly degraded after using Ti:Ash 40:60 and 60:40 by 45% and 41%, respectively under UV light. Doping metal ions significantly improved the photocatalyst visible light absorption where the band energy was reduced. It can be observed that Fe loading in the catalyst performed better than Ce under UV light, visible light, and natural visible light where Ti:Ash:Fe 40:55:05 and Ti:Ash:Ce 40:55:05 photocatalyst performed well. The Ti:Ash:Fe 40:55:05 and Ti:Ash:Ce 40:55:05 showed the best photocatalytic activity compared to other synthesized photocatalyst. The degradation rate of humic acid was achieved at 49% for Ti:Ash:Fe 40:55:05 and 45% for Ti:Ash:Ce 40:55:05 after 240 min of irradiation under visible light. The best parameters for the photocatalytic reaction were achieved by using Ti:Ash:Fe 40:55:5 and Ti:Ash:Ce 40:55:5 when catalyst to water mass ratio was set at 1:300 and tested for 120 minutes. Meanwhile, the Ti:Ash:Fe 40:55:05 degraded effectively 58% of humic acids after 120 minutes under UV light. However, 42% and 28% of humic acid degradation were observed when the Ti:Ash:Fe 40:55:05 was exposed to artificial visible light (420 nm) and natural light, respectively. The mechanism of the kinetic studies was performed for Humic acids photocatalytic reaction by using Langmuir-Hinshelwood kinetic rate expressions over the photocatalysts were adopting a hybrid photocatalyst. The specific reaction rate constant measured after 240 min under visible light of Ti:Ash:Fe 40:55:05 was 0.0028 min-1, whereas of Ti:Ash:Ce 40:55:05 under the same conditions, was 0.0025 min-1. Thus, the photocatalyst process has huge potential as an efficient alternative pre-treatment for seawater desalination.